Edukasi Manfaat Tanaman Obat dan Pengolahannya dengan Metode CBIA di Desa Bulusulur, Kabupaten Wonogiri, Jawa Tengah - Aris Widayati; Erna Tri Wulandari (Universitas Sanata Dharma, 2018)
The community service program reported in this paper aims to educate people about benefits of herbs and how to process herb raw materials for medication. This community service program was conducted in December 2016. The program involved 25 leaders of housewife communities (Kader PKK) in Bulusulur Village, Wonogiri, Central Java. The education was conducted using the CBIA (Cara Belajar Ibu Aktif) method. The CBIA supports the participants to be active during the education process. Results of the active learning through the CBIA method showed participants knowledge as folows: (1) participants were able to mention that herbal medicines are safe, have no side effects, can be easily obtained around their house; (2) they commonly used herbal for medication more than 4 times per month, obtained from their garden or local market; (3) they were able to mention the benefits of herbs commonly used; for example, temu lawak for stomachache, kunyit for pre-menstrual pain. However, they were not able to differentiate categories of herbal medicines which were produced by herbal manufacturers, such as Jamu, Obat Herbal Terstandar, and Fitofarmaka. Their knowledge about benefits of herbs was limited to those which were available in their garden. They also appreciated the demonstration of producing Bir Jawa and Sambiloto cookies.